Pengaruh ROA, CR dan NPM Terhadap Harga Saham Pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2021-2024 - Siti Chotimah; Mar’atus Solikah; Amin Tohari (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This research is motivated by the phenomenon of stock price fluctuations in manufacturing companies, which reflect market instability, both internal and external to the company. These volatile stock price changes create uncertainty for investors, particularly when financial performance indicators such as Return on Assets (ROA), Current Ratio (CR), and Net Profit Margin (NPM) show varying results across companies and time periods. Strong financial performance is usually a positive signal for investors, but inconsistencies in these indicators raise doubts in investment decision-making. The purpose of this study is to analyze the effect of ROA, CR, and NPM on stock prices in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. This study uses a quantitative approach with a causal research type, where the data used are secondary data obtained from the companies' annual financial reports. The sampling technique used was purposive sampling, with certain criteria, resulting in a sample of 85 companies. With an observation period of four years, a total of 340 observations were analyzed. The analysis was conducted using multiple linear regression with the help of SPSS version 30 software. The results of the analysis indicate that, partially, ROA and CR have a significant influence on stock prices. This means that increasing the efficiency of asset use and the company's ability to meet short-term obligations are important factors considered by investors. However, NPM does not have a significant influence partially on stock prices. Nevertheless, all three variables simultaneously have a significant influence on stock prices. This finding has important implications for company management, namely that increasing asset efficiency and optimal liquidity management can strengthen a company's attractiveness to investors by improving credible financial performance.